Kebijakan Hukum Dalam Sistem Peradilan Pidana Anak Dengan Pendekatan Keadilan Restoratif di Pengadilan Negeri Palembang - STA. Latief Hasjim; Erniwati Erniwati (Fakultas Hukum Universitas IBA Palembang, 2020)
Abstract This writing discusses the Legal Policy in the Child Criminal Justice System With the Restorative Justice Approach in the Palembang District Court. Criminal Law (KUHP) as well as in the special provisions of Law Number 11 Year 2012 concerning the Criminal Justice System for Children. Then in the implementation of the restoration in general has been going well in accordance with the provisions of the existing law in accordance with the trial according to the legal order so as to bring up negative which is a trauma that is feared to be used on the face. Many people involved in discussions about restoration in the form of diversion at the time of the prosecution or examination in court consider some of these factors, discuss about the preparation among various parties participating in research, help in correcting, correcting, assessing, assessing that which is contrary to the law in Palembang District Court is very likely that the performance of the juvenile judge is not yet optimal. For this reason, the writer, through this thesis, requests that and the need for policies to increase the number of children in Palembang District Court